Analisis Tingkat Kemampuan Pukulan Servis Tenis sebagai Dasar Pengembangan Pembelajaran Pendidikan Jasmani pada Klub Tenis Junior Manonjaya - Agustryani, Resty; Narlan, Abdul; Subekti, Nuriska; Pratama, Tegar Maesabudi (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to determine the level of tennis service skills among junior athletes at the Manonjaya Tennis Club in 2024. The background of this study is based on the importance of mastering service techniques as a basic skill in tennis that plays a major role in scoring points in a match. The research method used is quantitative descriptive with a survey technique. The research population consisted of 20 athletes, with a sample of 12 junior athletes (8 boys and 4 girls) aged 10–14 years selected using purposive sampling. The research instrument was the Hewitt tennis test, which consisted of 10 service skill trials assessed based on ball placement accuracy. Data analysis used descriptive percentage statistics. The results showed that the average service ability of the athletes was 40% with a median of 40.5, a mode of 41, a minimum value of 37, a maximum value of 43, and a standard deviation of 2.88. A total of 67% of athletes were in the high category (Grade B), while the other 33% were in the medium category (Grade C). The conclusion of this study is that the service ability of junior athletes at the Manonjaya Tennis Club is relatively good, although there are still athletes who need further training. This study recommends the need for more focused training in physical, technical, and mental aspects of competition so that the quality of athletes' serves can improve consistently.